Volume-Image: The Future as Memory in Thierry Kuntzel’s Video Installation The Waves (2003) - Nony, Anaïs (Intermédialités / Intermediality, 2019)
Video-objects are often discussed in terms of their ability to reflect upon the speed of our narcissistic culture, but less acknowledged is video’s agency to perform electronic events outside of human experience. This article engages in scholarship interested in the space of video operations where lived and imagined, real and virtual phenomena are experienced at the threshold of perception. Bringing into this conversation a discussion of The Waves (2003), an interactive installation by video pioneer and media critic Thierry Kuntzel, the article moves away from the time/movement nexus grounded in a filmic understanding of the image to position video-memory as the emergence of a volume of time. Different from the time-image and movement-image of cinema, the volume-image of video defines a mode of engaging with multiple temporalities within the continuum of the video itself. Constituted progressively through layers of ever-changing signal processes, the volume-image of video technology is an open field, a transductive zone where multiple intensities create new representational rhythms, which disrupt the durational model of time so often attached to human experience.